Construction of Company Self-Image Through Social Media Instagram in Semiotic Review - Nuryanti, Desi Eka (Universitas Muhammadiyah Yogyakarta, 2023)
This article aims to analyze Bakpia Tugu Jogja's self-image through Instagram social media. This research is a field research with a qualitative approach. The problem raised by the author is: How is the construction of Bakpia Tugu Jogja's self-image on Instagram social media based on Ferdinand De Saussure's semiotic analysis? The focus of the research is Instagram Bakpia Kukus Tugu Jogja @bakpiatugujogja. The result obtained is that Bakpia Kukud Tugu Jogja has succeeded in building a self-image as food or souvenirs typical of Jogja. Bakpia Kukus Tugu Jogja has also succeeded in building an elegant image of local products.